Type 2 Diabetes Mellitus Remission in Patients with Ideal BMI in Rivers State, Nigeria (Global Journal of Medical Research, 2023)
Background When Type 2 Diabetes patients are in resource-restrained environments with little access to sustainable care weight increase is linked to poor glycemic control from insulin resistance Safer locally accessible and scientifically supported methods of managing their health become a priority when they lack effective access to medical treatment and medicines as a result of poverty Targeted lifestyle therapies have been shown to be clinically beneficial and reasonably priced for the prevention and management of diabetes today This research seeks to assess the effectiveness of a purely Nigerian diet in helping people with type 2 diabetes mellitus lose weight and maintain excellent glycaemic control Method Randomization was used to divide the sixty research participants into treatment dietary caloric restriction intervention and control standard of care groups that were matched Samples were gathered for analysis at baseline midline and at the conclusion of the trial throughout the participants 24-week follow-up period
Keywords: type 2 diabetes; diet; intervention; hba1c; glycaemic control; remission; waist circumference and BMI